2021
DOI: 10.1016/j.ijso.2021.100392
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ketofol versus propofol induction on hemodynamic profiles in adult elective surgical patients: A Randomized Controlled Trial

Abstract: Background: Most of the time propofol and ketamine have been used as an induction agent in adult surgical patients but propofol may cause cardiorespiratory depression while ketamine increases heart rate and arterial blood pressure. On the other hand, the clinical effects of propofol and ketamine seem to be complementary. Ketofol is most commonly used for procedural sedation hence exploring its effectiveness for induction will be paramount for the clinical care of surgical patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Ketofol in ratio 1:1, 1:2 has been used in some studies as induction agent in patients undergoing laparotomy or laproscopic surgery and better hemodynamic stability was observed in the group receiving combination of drug. 11,12,13 Smichney NJ et al performed a study in critically ill pts requiring intubation and they compared propofol and ketofol as induction agent in these pts the results were similar to our study i.e. hemodynamic stability in ketofol group while hypotension and bradycardia in propofol group.…”
Section: Discussionsupporting
confidence: 86%
“…Ketofol in ratio 1:1, 1:2 has been used in some studies as induction agent in patients undergoing laparotomy or laproscopic surgery and better hemodynamic stability was observed in the group receiving combination of drug. 11,12,13 Smichney NJ et al performed a study in critically ill pts requiring intubation and they compared propofol and ketofol as induction agent in these pts the results were similar to our study i.e. hemodynamic stability in ketofol group while hypotension and bradycardia in propofol group.…”
Section: Discussionsupporting
confidence: 86%
“…4 However, the Hemodynamic instability poses a significant challenge during anesthesia and surgery, often arising from the stresses of intubation, surgical incisions, and the administration of anesthetic drugs. 5 This issue is especially common among patients with heart conditions and older adults. 5,6 Hemodynamic disturbances are frequently seen during the start and end of anesthesia.…”
Section: Original Articlementioning
confidence: 99%
“…5 This issue is especially common among patients with heart conditions and older adults. 5,6 Hemodynamic disturbances are frequently seen during the start and end of anesthesia. Low blood pressure is a common occurrence when propofol is used for anesthesia induction, leading to a notable drop in blood pressure, particularly in patients with high blood pressure.…”
Section: Original Articlementioning
confidence: 99%
“…This effect was further supported in clinical studies in humans when ketamine was administered concurrently with propofol (a combination known as ketofol). Ketofol can lead to improved hemodynamics and respiratory function compared to propofol alone 155‐157 . In a clinical study in humans with refractory SE, ketofol was successful in terminating seizure activity.…”
Section: Third‐line Treatmentmentioning
confidence: 99%
“…Ketofol can lead to improved hemodynamics and respiratory function compared to propofol alone. 155 , 156 , 157 In a clinical study in humans with refractory SE, ketofol was successful in terminating seizure activity. In the same study, it was reported that the short‐term or prolonged infusion of ketamine, with or without propofol infusion, was also effective in controlling super‐refractory SE.…”
Section: Third‐line Treatmentmentioning
confidence: 99%